OFFERING CEREMONY “SEDEKAH LAUT, IN CENTRAL JAVA - Triyanto Triyanto; Sumarwati Sumarwati; Kundharu Saddhono (Universitas Sebelas Maret, 2019)
The cultural ceremony known as the Sedekah Laut is a ceremony held once a year, more precisely at the beginning of Shura month. This ceremony intends to give one a request for more abundant seafood than before. Sedekah Lautis related to the offering or named with alms to the Queen of South. This study aims to describe how the event of Sedekah Laut ritual in Cilacap. The method used in this research is observation and interview. This research is useful to increase the knowledge about culture in the archipelago for the readers and for the general public. The results indicate that the ritual has several functions for society that include social, cultural, economic, and religious dimensions. The special functions of the ceremony are to thank the Almighty God for his mercy to bless the community with the rest of the fish subsistence and to pray for the salvation of life